Characterization of a novel PQQ-dependent quinohemoprotein pyranose dehydrogenase from Coprinopsis cinerea classified into auxiliary activities family 12 in carbohydrate-active enzymes. - Kouta Takeda; Hirotoshi Matsumura; Takuya Ishida; Masahiro Samejima; Hiroyuki Ohno; Makoto Yoshida; Kiyohiko Igarashi; Nobuhumi Nakamura (PLoS ONE, 2015)
The basidiomycete Coprinopsis cinerea contains a quinohemoprotein (CcPDH named as CcSDH in our previous paper), which is a new type of pyrroloquinoline-quinone (PQQ)-dependent pyranose dehydrogenase and is the first found among all eukaryotes. This enzyme has a three-domain structure consisting of an N-terminal heme b containing a cytochrome domain that is homologous to the cytochrome domain of cellobiose dehydrogenase (CDH; EC 1.1.99.18) from the wood-rotting basidiomycete Phanerochaete chrysosporium, a C-terminal family 1-type carbohydrate-binding module, and a novel central catalytic domain containing PQQ as a cofactor. Here, we describe the biochemical and electrochemical characterization of recombinant CcPDH. UV-vis and resonance Raman spectroscopic studies clearly reveal characteristics of a 6-coordinated low-spin heme b in both the ferric and ferrous states, as well as intramolecular electron transfer from the PQQ to heme b. Moreover, the formal potential of the heme was evaluated to be 130 mV vs. NHE by cyclic voltammetry. These results indicate that the cytochrome domain of CcPDH possesses similar biophysical properties to that in CDH. A comparison of the conformations of monosaccharides as substrates and the associated catalytic efficiency (kcat/Km) of CcPDH indicates that the enzyme prefers monosaccharides with equatorial C-2, C-3 hydroxyl groups and an axial C-4 hydroxyl group in the 1C4 chair conformation. Furthermore, a binding study shows a high binding affinity of CcPDH for cellulose, suggesting that CcPDH function is related to the enzymatic degradation of plant cell wall.